Alginic acid salt-based potassium niobium sulfide composite microspheres, a preparation method therefor, and use thereof

CN116651404BActive Publication Date: 2026-10-30NAVAL UNIV OF ENG PLA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310858727.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2026-10-30
Estimated Expiration
2043-07-13

AI Technical Summary

Technical Problem

然而以上吸附材料对90Sr选择性吸附能力仍然有限

Benefits of technology

[0018]1、本发明通过将硫化铌钾(KSnS)粉末与海藻酸钠(NaALG)混合形成的混合浆液滴入凝固浴中成球,制备出ALG-KNbS复合微球,所述复合微球结合了无机吸附材料和有机吸附材料的优点,保证高吸附容量及选择性的前提下,对锶有较强选择性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116651404B_ABST
    Figure CN116651404B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of alginate-based potassium niobium sulfide composite microspheres and its preparation method, application, preparation steps are as follows: take anhydrous K2CO3 and grind into powder, S powder and Nb powder are mixed uniformly in turn, then add deionized water and mix uniformly to carry out hydrothermal reaction, after reaction, the product is washed, filtered, dried, ground to obtain potassium niobium sulfide;Alginic acid salt-based and potassium niobium sulfide are dispersed in deionized water, first solvent is added and mixed uniformly, to obtain mixed slurry, mixed slurry is in the form of droplets, under the pressure of setting, drop into CaCl2 solution to obtain gel microspheres, after cleaning, drying, obtain alginate-based potassium niobium sulfide composite microspheres.The composite microspheres have stronger selectivity and greater adsorption capacity for strontium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wastewater treatment technology, specifically to an alginate-based potassium niobium sulfide composite microsphere, its preparation method, and its application. Background Technology

[0002] In recent years, while nuclear energy and nuclear technology have brought tremendous convenience to our lives, the disposal of radioactive waste generated during their application has also attracted widespread attention. Therefore, the proper, economical, and efficient disposal of radioactive waste plays a crucial role in promoting the development of the nuclear industry and the widespread use of nuclear energy. The most typical and hazardous long-lived radionuclides in radioactive wastewater are mainly divided into two categories: fission products... 137 Cs, 90 Sr and other activated products 60 Co, 59 Fe, 56 Mn, etc. Among them, 90 Sr is a highly toxic radionuclide with a long half-life of 28.5 years, classifying it as a long-lived radionuclide. Adsorption methods can target low- to medium-level radioactive wastewater by adsorbing long-lived, high-volume, and highly toxic radionuclides, thereby minimizing waste. Currently, adsorbents for strontium both domestically and internationally mainly include inorganic adsorbents such as pyrochlore-type metal oxides, fluorophlogopite, metal sulfides, titanates, and titanosilicones, as well as organic adsorbents such as alginate, chitosan, and graphene oxide. However, the above adsorbents have limitations in... 90 The selective adsorption capacity of Sr remains limited. Summary of the Invention

[0003] This invention provides an alginate-based potassium niobium sulfide composite microsphere, its preparation method, and its application. Combining the advantages of alginate and potassium niobium sulfide adsorbents, it ensures high adsorption capacity and selectivity, thus preparing a microsphere suitable for adsorption... 90 Sr selectively adsorbed composite microspheres.

[0004] The present invention provides the following solution to the above-mentioned technical problems: an alginate-based potassium niobium sulfide composite microsphere, wherein the composite microsphere uses sodium alginate spheres as a substrate, and the potassium niobium sulfide is uniformly distributed within the sodium alginate spheres; the particle size of the composite microsphere is 0.4–0.1 mm.

[0005] The preparation method of alginate-based potassium niobium sulfide composite microspheres as described above includes the following steps:

[0006] 1) Anhydrous K2CO3 was ground into powder and mixed with S powder and Nb powder in a hydrothermal reactor. Then, deionized water was added and mixed evenly to carry out the hydrothermal reaction. After the reaction was completed, the product was washed several times with acetone and deionized water, filtered, and dried under vacuum at 100°C to obtain potassium niobium sulfide (KSnS). It was then ground into fine powder with a particle size of less than 0.1 mm.

[0007] 2) Disperse sodium alginate and potassium niobium sulfide in deionized water, add the first solvent and mix evenly to obtain a mixed slurry. The mixed slurry is dropped into CaCl2 solution under a set pressure through a spheroidizing device to obtain gel microspheres. The microspheres are acid-washed several times with 0.1 mol / L acetic acid and then washed several times with deionized water. The washed microspheres are placed in a drying oven and dried at 30℃ for 24 h to obtain alginate-based potassium niobium sulfide (ALG-KNbS) composite microspheres.

[0008] Preferably, in step 1), the mass ratio of sulfur powder, K2CO3, and Nb powder is 4-5:3-4:4.5-5.5. More preferably, in step 1), the mass ratio of sulfur powder, K2CO3, and Nb powder is 4:4:5.5.

[0009] Preferably, in step 1), the hydrothermal reaction temperature is 180–220°C, and the reaction time is 16–20 h. More preferably, the hydrothermal reaction temperature is 220°C, and the reaction time is 18 h.

[0010] Preferably, in step 2), the first solvent is one of di(2-ethylhexyl) phthalate, diisononyl phthalate, dimethyl phthalate, and dibutyl phthalate. More preferably, in step 2), the first solvent is di(2-ethylhexyl) phthalate.

[0011] Preferably, in step 2), the concentration of sodium alginate is 0.5–4 wt%, and the concentration of potassium niobium sulfide is 2–16 wt%. Preferably, in step 2), the concentration of sodium alginate is 2 wt%, and the concentration of potassium niobium sulfide is 8 wt%.

[0012] Preferably, in step 2), the concentration of CaCl2 is 0.5–5 wt%. More preferably, in step 2), the concentration of CaCl2 is 4 wt%.

[0013] Preferably, in step 2), the pressure is set to 10-50 kPa. More preferably, in step 2), the pressure is set to 40 kPa.

[0014] Preferably, in step 2), the sphere-forming device includes a cross-shaped glass tube and multiple syringes. The syringe needle is fitted inside the vertical tube of the cross-shaped glass tube. The piston rod of the syringe is driven by an injection pump. The outlet end of the vertical tube of the cross-shaped glass tube leads to a collector. The collector is used to fill CaCl2 solution and collect alginate-based microspheres. The inlet end of the horizontal tube of the cross-shaped glass tube is connected to the outlet end of a drying device. The inlet end of the drying device is connected to the output end of an air compressor.

[0015] The drying device can consist of a wide-mouth bottle, a short L-shaped gas guide tube, a long L-shaped gas guide tube with a rubber stopper, and a desiccant. The short L-shaped gas guide tube and the long L-shaped gas guide tube are fixed to the mouth of the wide-mouth bottle by the rubber stopper. The wide-mouth bottle is filled with a desiccant (such as concentrated sulfuric acid). The inlet end of the short L-shaped gas guide tube is connected to the wide-mouth bottle but does not contact the desiccant. The outlet end of the short L-shaped gas guide tube is connected to the inlet end of the horizontal tube of the cross-shaped glass tube. The outlet end of the long L-shaped gas guide tube is connected to the wide-mouth bottle and contacts the desiccant. The inlet end of the long L-shaped gas guide tube is connected to the output end of the air compressor.

[0016] The above-mentioned application of alginate-based potassium niobium sulfide composite microspheres in the treatment of strontium-containing wastewater.

[0017] The beneficial effects of this invention are:

[0018] 1. This invention prepares ALG-KNbS composite microspheres by dropping a mixed slurry formed by mixing potassium niobium sulfide (KSnS) powder and sodium alginate (NaALG) into a coagulation bath to form spheres. The composite microspheres combine the advantages of inorganic and organic adsorbent materials, ensuring high adsorption capacity and selectivity while exhibiting strong selectivity for strontium.

[0019] 2. This invention provides a microsphere generation device, in which air is transported by an air compression device. The air passes through the horizontal tube of the cross-shaped glass tube, and the branch flow formed in the vertical tube becomes a shear force, causing the slurry in the syringe pushed by the injection pump to form uniform micro-droplets at the needle tip. This solves the problems of low droplet formation rate, inconvenience for mass production, large particle size, and poor adsorption effect of traditional syringes.

[0020] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Specific embodiments of the present invention are given in detail below with reference to the accompanying drawings. Attached Figure Description

[0021] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this application, illustrate exemplary embodiments of the invention and, together with their description, serve to explain the invention and do not constitute an undue limitation thereof. In the drawings:

[0022] Figure 1 A schematic diagram of the process for preparing ALG-KNbS composite microspheres in Example 1;

[0023] Figure 2 This is a schematic diagram of the microsphere generation device used in the preparation of ALG-KNbS composite microspheres in Example 1.

[0024] Figure 3 SEM images of ALG-KNbS composite microspheres prepared in Example 1;

[0025] Figure 4 The effect of adsorption time on Sr in ALG-KNbS composite microspheres in Example 2 2+ A diagram illustrating the change in removal rate;

[0026] Figure 5 The effect of simulated wastewater pH on the effect of ALG-KNbS composite microspheres on Sr in Example 3 2+ A diagram illustrating the change in removal rate;

[0027] Figure 6 Sr in the simulated wastewater of Example 4 2+ Initial concentration of ALG-KNbS composite microspheres on Sr 2+ A diagram illustrating the change in removal rate.

[0028] The attached diagram lists the components represented by each number as follows:

[0029] 1. Cross-shaped glass tube; 2. Syringe; 3. Injection pump; 4. Collector; 5. Drying device; 6. Drying air compressor. Detailed Implementation

[0030] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.

[0031] The working principle of this invention is as follows:

[0032] The preparation of ALG-KNbS composite microspheres utilizes NaALG solution reacting with high concentrations of Ca... 2+ The principle behind the rapid cross-linking reaction and gel formation in aqueous solutions is that hydrochloric acid is used to wash away excess calcium residue on the surface. 2+ The water was washed away, and some of the calcium alginate (CaALG) adsorbed by KNbS was replaced. 2+The purpose of adding a small amount of DEHP is to make the KNbS powder mix more evenly and to improve the flexibility of the prepared gel microspheres. The cross-linking reaction equation is: 3(C6H7NaO6) n +nCaCl2+nH2O+nH + ——→(C 18 H 24 CaO 19 ) n +2nNaCl+nNa +

[0033] because 60 The stable nuclides of Sr and strontium have very similar chemical properties, therefore, stable nuclides can be used to simulate adsorption experiments. 60 The adsorption performance of ALG-KNbS was tested using static adsorption experiments. The specific experimental design and results are as follows:

[0034] Preparation of low concentrations of Sr 2+ The simulated wastewater was poured into a stoppered conical flask, and adsorbent material was added at a solid-liquid ratio of 0.02 g: 50 mL. Specific amounts of sodium chloride, calcium chloride, magnesium chloride, and potassium chloride were added as coexisting ions as needed. After adjusting the pH of the solution, it was placed in a DKZ series electrically heated constant-temperature shaking water bath, with the temperature adjusted to 40℃ and the shaking frequency set to 80–100 min. -1 Under these conditions, the adsorption time and Sr were studied separately using the controlled variable method. 2+ The effects of initial concentration, coexisting ion species and concentrations, and solution pH on the adsorption effect of the material were investigated. Adsorption performance can be characterized by removal rate (R, %) and adsorption capacity (Q, mg / g), calculated using the following formulas:

[0035]

[0036]

[0037] Where: C i The initial concentration of the target ion (mg / L), C e denoted as , where V is the equilibrium concentration of the target ion (mg / L), V is the solution volume (mL), and m is the adsorbent mass (g).

[0038] Example 1

[0039] like Figure 1 As shown in the figure, this embodiment provides a method for preparing alginate-based potassium niobium sulfide composite microspheres, as detailed below:

[0040] I. Preparation of potassium niobium sulfide (KNbS)

[0041] 1. Take an appropriate amount of K2CO3 powder, Nb powder and S powder and add them to a hydrothermal reactor. Add a small amount of deionized water to the reactor and stir evenly. React at 220℃ for 18 hours. Wash the product several times with acetone and deionized water, filter and dry under vacuum at 100℃ to obtain KSnS. Grind it into fine powder with a particle size of less than 0.1 mm.

[0042] 2. The effects of varying the amounts of each raw material on the yield of KNbS were investigated, as shown in Table 1.

[0043] Table 1. Effect of the amount of each raw material on the preparation of KNbS

[0044]

[0045] The optimal amounts of each reactant in the preparation of KNbS are 4g S powder, 5.5g Nb powder, and 4g K2CO3, corresponding to a maximum yield of 71% for KNbS.

[0046] II. Preparation of ALG-KNbS composite microspheres

[0047] 1. Sodium alginate (NaALG) and KNbS powder are mixed and dispersed in deionized water, and a small amount of di(2-ethylhexyl) phthalate (DEHP) is added to obtain a mixed slurry.

[0048] 2. For example Figure 2 As shown, syringe 2 draws up the mixed slurry. The syringe 2's needle is fitted inside the vertical tube of the cross-shaped glass tube 1. The piston rod of syringe 2 contacts the output end of the injection pump 3. The inlet end of the water level tube of the cross-shaped glass tube 1 is connected to the outlet end of the short L-shaped gas guide tube of the drying device 5. The inlet end of the short L-shaped gas guide tube leads to the wide-mouth bottle of the drying device 5, but does not contact the concentrated sulfuric acid filled in the wide-mouth bottle. The inlet end of the long L-shaped gas guide tube of the drying device 5 is connected to the outlet of the air compressor 6. The outlet end of the long L-shaped gas guide tube is submerged in the concentrated sulfuric acid filled in the wide-mouth bottle. The short L-shaped gas guide tube and the long L-shaped gas guide tube are fixed to the mouth of the wide-mouth bottle by a rubber stopper. The outlet end of the vertical tube of the cross-shaped glass tube 1 leads to the collector 4, which contains CaCl2 solution.

[0049] 3. Start the air compressor 6 and the injection pump 3, control the air pressure, mix the slurry and drip it into the coagulation bath (CaCl2 solution) to obtain gel microspheres. Wash them several times with 0.1 mol / L acetic acid, and then wash them several times with deionized water. Place the washed microspheres in a drying oven and dry them at 30℃ for 24 hours to obtain ALG-KNbS composite microspheres.

[0050] 4. The CaCl2 concentration was controlled at 5% and the air pressure at 40 kPa. The effects of microspheres prepared with different NaALG concentrations were investigated, as shown in Table 2.

[0051] Table 2 Effect of NaALG concentration on pelleting effect

[0052]

[0053] As shown in Table 2, the optimal concentration of NaAlg solution is 2%, at which point microspheres with good spherical shape can be prepared.

[0054] 5. The NaAlg solution concentration was controlled at 2%, and the air pressure at 40 kPa. The effects of microspheres prepared with different CaCl2 concentrations were investigated, as shown in Table 3.

[0055] Table 3 Effect of CaCl2 concentration on pelletizing effect

[0056]

[0057] As shown in Table 3, the optimal concentration of CaCl2 solution is 4%, at which point microspheres with good spherical shape can be prepared.

[0058] 6. The concentrations of NaAlg solution and CaCl2 solution were controlled at 2% and 4%, respectively, and the effects of microspheres prepared under different air pressures were investigated, as shown in Table 4:

[0059] Table 4. Effect of air pressure on particle size of alginate-based spherical composite microspheres

[0060]

[0061] Ion exchange resins typically have a diameter between 0.3 mm and 1.2 mm. Too small a diameter significantly increases fluid resistance during column packing, reducing production efficiency. Too large a diameter results in a smaller specific surface area, decreasing adsorption capacity. This paper selects microspheres with a particle size range of 0.4 mm to 1 mm for further adsorption experiments. As shown in the table, the optimal air pressure for preparing ALG-based spherical composite microspheres is 40 kPa.

[0062] The optimal raw material conditions for preparing ALG-KNbS composite microspheres are: an air pressure of 40 kPa, 2% NaAlg aqueous solution dispersing 8% KNbS by mass, and a 4% CaCl2 solution as the coagulation bath (ALG-KNbS composite microspheres prepared in serial number 14).

[0063] Electron micrograph of the microsphere obtained in sequence 14 is as follows: Figure 3As shown, ALG-KNbS consists of spherical particles with a diameter of approximately 0.5 mm and a relatively rough surface. The irregular material surface has many grooves, which to some extent increases the specific surface area of ​​the material. It can be seen that the ALG-based composite material is formed by the infiltration of KNbS into the interior of ALG followed by deposition. The cracks generated during the deposition process facilitate the deposition of Sr. 2+ It penetrates the interior of the material, accelerating the adsorption rate of the composite material.

[0064] Example 2

[0065] This embodiment provides Example 1, No. 14, which describes the preparation of ALG-KNbS composite microspheres as an adsorbent for treating radioactive wastewater, and explores the effect of adsorption time on Sr. 2+ The effects of adsorption efficiency are explained in the following steps:

[0066] Preparation of Sr 2+ A single-component aqueous solution with a concentration of 5 mg / L was used as the simulated wastewater to be treated. 50 mL of Sr-containing solution was added to a stoppered conical flask. 2+ Simulated wastewater was treated with 0.02 g of adsorbent, and the mixture was placed in a stoppered conical flask in a constant-temperature shaking water bath. The reaction was carried out continuously at 40°C. At predetermined time intervals, the stoppered conical flasks were removed sequentially, and the adsorbent was separated. The supernatant was collected as the post-adsorption solution, and the Sr content in the solution was determined using atomic absorption spectrometry. 2+ The concentration, the results are as follows Figure 4 As shown.

[0067] In the first 20 minutes of the adsorption reaction, ALG-KNbS composite microspheres showed a high adsorption capacity for Sr. 2+ The removal rate of Sr increased rapidly. Under experimental conditions, ALG-based materials showed improved removal efficiency for Sr. 2+ The adsorption of Sr reaches equilibrium in approximately 80 minutes. At adsorption equilibrium, ALG-KNbS exhibits [a certain adsorption capacity / effect]. 2+ The removal rate was 98.4%, and the adsorption capacity was 12.3 mg / g.

[0068] Example 3

[0069] This embodiment provides Example 1, No. 14, which describes the preparation of ALG-KNbS composite microspheres as an adsorbent for treating radioactive wastewater, and explores the effect of solution pH on Sr. 2+ The effects of adsorption efficiency are explained in the following steps:

[0070] Prepare Sr separately 2+ A 5 mg / L aqueous solution was used as the simulated wastewater to be treated. 50 mL of Sr-containing solution was added to stoppered conical flasks of different numbers. 2+Simulated wastewater was treated with 0.02 g of adsorbent. The pH of the solution was adjusted using 1% HCl, 10% HCl, 0.1 mol / L NaOH, and 1 mol / L NaOH, respectively. The stoppered conical flask was placed in a constant-temperature shaking water bath. The reaction was carried out continuously at 40°C. After the adsorbent reached adsorption equilibrium, the stoppered conical flask was removed, the adsorbent was separated, and the supernatant was collected as the post-adsorption solution. The Sr content in the solution was determined using atomic absorption spectrometry. 2+ The concentration, the results are as follows Figure 5 As shown.

[0071] ALG-KNbS for Sr under acidic conditions 2+ The removal rate showed a significant decrease. This is because ALG is a pH-sensitive gel; in an acidic environment, its structural pores shrink, making the diffusion of target ions more difficult, thus affecting the full contact between the target ions and the active substances. Simultaneously, the abundant H₂ present in an acidic environment... + It will also become Sr 2+ Competition for ions affects the adsorption efficiency of Sr. ALG-KNbS exhibits better adsorption performance for Sr in the pH range of 7–10. 2+ It has a good adsorption effect, with a removal rate that can generally be maintained above 90%, and has a wide pH adaptability.

[0072] Example 4

[0073] This embodiment provides Example 1, No. 14, the preparation of ALG-KNbS composite microspheres as an adsorbent for treating radioactive wastewater, and explores the Sr in the wastewater. 2+ Initial concentration of Sr 2+ The effects of adsorption efficiency are explained in the following steps:

[0074] Prepare Sr separately 2+ Solutions with initial concentrations of 5 mg / L, 10 mg / L, 20 mg / L, 50 mg / L, 100 mg / L, and 200 mg / L were prepared. The adsorbent was added to each stoppered conical flask at a solid-liquid ratio of 0.02 g: 50 mL, and the reaction was carried out continuously at 40 °C. After the adsorbent reached adsorption equilibrium, the stoppered conical flasks were removed, the adsorbent was separated, and the supernatant was collected as the post-adsorption solution. The Sr content in the solution was determined using atomic absorption spectrometry. 2+ The concentration, the results are as follows Figure 6 As shown.

[0075] While maintaining the pH of the simulated wastewater at neutral, as the Sr in the solution... 2+ With increasing initial concentration, ALG-KNbS affects Sr 2+ The adsorption capacity gradually increases. When the Sr in the solution... 2+ At an initial concentration of 100 mg / L, ALG-KNbS reached adsorption saturation, with a saturation adsorption capacity of 64.25 mg / g.

[0076] Example 5

[0077] This embodiment provides Example 1, No. 14, which describes the preparation of ALG-KNbS composite microspheres as an adsorbent for treating radioactive wastewater, and explores the effect of coexisting ions and their concentrations in the wastewater solution on Sr. 2+ The effects of adsorption efficiency are explained in the following steps:

[0078] Prepare Sr separately 2+ A 5 mg / L aqueous solution was used as the simulated wastewater to be treated. NaCl, KCl, CaCl2, MgCl2, etc. were added to adjust the coexisting cations Na+ in the solution. + Mg 2+ K + Ca 2+ The concentration of Sr was determined. Adsorbent was added to each stoppered conical flask at a solid-liquid ratio of 0.02 g: 50 mL, and the reaction was carried out continuously at 40 °C. After the adsorbent reached adsorption equilibrium, the stoppered conical flasks were removed, the adsorbent was separated, and the supernatant was taken as the post-adsorption solution. The concentration of Sr in the solution was determined using atomic absorption spectrometry. 2+ The concentrations were determined, and the results are shown in Table 5.

[0079] Table 4. Effects of ALG-KNbS microspheres on Sr under different ion concentrations. 2+ Removal rate (%)

[0080]

[0081] The coexistence of divalent ions affects the adsorption of Sr by ALG-KNbS. 2+ The effect is far greater than that of monovalent ions. At 20 times and 100 times that of Sr... 2+ Concentration of Ca 2+ and Mg 2+ In the case of coexistence, ALG-KNbS affects Sr 2+ The removal rates were still 32.2% and 38.2%, indicating that ALG-KNbS effectively removed Sr. 2+ It has a high degree of selectivity.

[0082] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Those skilled in the art can readily implement the present invention based on the accompanying drawings and the above description. However, any modifications, alterations, or variations made by those skilled in the art without departing from the scope of the present invention, utilizing the disclosed technical content, are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, or variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing alginate-based potassium niobium sulfide composite microspheres, characterized in that, Includes the following steps: 1) Anhydrous K2CO3 was ground into powder, and then mixed with S powder and Nb powder in sequence. Deionized water was then added and mixed evenly to carry out a hydrothermal reaction. After the reaction was completed, the product was washed, filtered, dried and ground to obtain potassium niobium sulfide. 2) Disperse sodium alginate and potassium niobium sulfide in deionized water, wherein the concentration of sodium alginate is 0.5~4wt% and the concentration of potassium niobium sulfide is 2~16wt%; then add a first solvent and mix evenly to obtain a mixed slurry. The mixed slurry is dropped into a 0.5~5wt% CaCl2 solution at 10~50kPa through a spheroidizing device to obtain gel microspheres. After washing and drying, alginate-based potassium niobium sulfide composite microspheres are obtained. The alginate-based potassium niobium sulfide composite microspheres have sodium alginate spheres as the base, and potassium niobium sulfide is uniformly distributed in the sodium alginate spheres. The particle size of the composite microspheres is 0.4~1mm. The first solvent is one of di(2-ethylhexyl) phthalate, diisononyl phthalate, dimethyl phthalate, and dibutyl phthalate.

2. The method for preparing alginate-based potassium niobium sulfide composite microspheres according to claim 1, characterized in that, In step 1), the mass ratio of S powder, K2CO3, and Nb powder is 4~5:3~4:4.5~5.

5.

3. The method for preparing alginate-based potassium niobium sulfide composite microspheres according to claim 1, characterized in that, In step 1), the hydrothermal reaction temperature is 180~220℃ and the reaction time is 16~20h.

4. The method for preparing alginate-based potassium niobium sulfide composite microspheres according to claim 1, characterized in that, In step 2), the sphere-forming device includes a cross-shaped glass tube (1) and multiple syringes (2). The needle tube of the syringe (2) is fitted inside the vertical tube of the cross-shaped glass tube (1). The piston rod of the syringe (2) is pushed by the injection pump (3). The outlet end of the vertical tube of the cross-shaped glass tube (1) is connected to the collector (4). The collector (4) is used to fill the coagulation bath and collect alginate-based microspheres. The inlet end of the horizontal tube of the cross-shaped glass tube (1) is connected to the outlet end of the drying device (5). The inlet end of the drying device (5) is connected to the output end of the air compressor (6). The drying device (5) is used to dry the air output by the air compressor (6).

5. The application of alginate-based potassium niobium sulfide composite microspheres prepared according to any one of claims 1 to 4 in the treatment of strontium-containing wastewater.

Citation Information

Patent Citations

  • Calcium alginate-copric ferrocyanide composite ion exchange agent and preparation method thereof

    CN109865537A

  • Quick and controllable preparation method of three-dimensional graphene microspheres for adsorption

    CN109896519A